Immobilization of lipase on poly(N-vinyl-2-pyrrolidone-co-2-hydroxyethyl methacrylate) hydrogel for the synthesis of butyl oleate - Basri, M.; Wong, C. C.; Ahmad, M. B.; Razak, C. N. A.; Salleh, A. B. (Wiley, 1999)
Lipase from Candida rugosa was immobilized by entrapment on poly(N-vinyl-2-pyrrolidone-co-2-hydroxyethyl methacrylate) [poly(VP-co-HEMA)] hydrogel, cross-linked with ethylene glycol dimethacrylate (EDMA). The immobilized enzyme was used in the esterification of oleic acid with butanol in hexane. The activities of the immobilized enzyme preparations and the leaching of the enzyme from the hydrogel supports with respect to composition were investigated. The thermal, solvent, and storage stability of the immobilized preparations also were determined. Increasing the percentage VP from 0 to 90, which corresponds to the increase in the hydrophilicity of the hydrogels, increased the activity of the immobilized enzyme. Lipase immobilized onto VP(%):HEMA(%), 90:10 hydrogel had the highest activity. Increasing the hydrophobicity of the hydrogel (increasing the percentage HEMA) seemed to decrease leaching of the enzyme from the support. Immobilized lipase on 100% HEMA hydrogel indicated highest entrapment and lowest leaching by hexane washing. The lipase immobilized on VP(%):HEMA(%), 50:50 hydrogel showed highest thermal, solvent, and storage stability compared to lipase immobilized on other hydrogel compositions as well as the native lipase.